THE UNIQUE OUTCROPS OF UPPER JURASSIC DEPOSITS IN UKRAINIAN PRECARPATHIAN - Zhabina, N.; Anikeyeva, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of field studies the Upper Jurassic deposits in outcrops in the valley of the Dniester river are given. The most representative outcrops are described. The age, facies composition, stratigraphic attachments and correlation of these deposits in outcrops and in well-sections are defined. These illustrated by geological profiles and photos.